The present as history : essays and reviews on capitalism and socialism - Sweezy, Paul M. (New York US: Monthly Review Press, 1953)
Recopila los discursos pronunciados por Fidel Castro en Chile en 1971.
Keywords: HISTORIA; CAPITALISMO; SOCIALISMO; IMPERIALISMO; MARXISMO